2014
DOI: 10.1007/978-1-4939-2269-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast-Based High-Throughput Screens for PKA Pathway Inhibitors and Activators

Abstract: Features of the fission yeast Schizosaccharomyces pombe cAMP/PKA pathway make S. pombe particularly amenable for heterologous expression of cAMP pathway proteins such as GαS subunits and their cognate adenylyl cyclases, PKA catalytic and regulatory subunits, and cyclic nucleotide phosphodiesterases. We have constructed two PKA-repressed reporters for use in high-throughput screens to detect compounds that elevate or reduce PKA activity, thus facilitating the discovery of both inhibitors and activators of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…5 A ). Expression of a PKA-repressed fbp1-GFP reporter for which PDE inhibition represses GFP expression [21, 24] confirmed the reduced sensitivity of PDE4B2 T407A to BC54 and rolipram (Fig. 5 B ), although PDE4B T407A appears to be inhibited by high levels of both compounds.…”
Section: Resultsmentioning
confidence: 82%
“…5 A ). Expression of a PKA-repressed fbp1-GFP reporter for which PDE inhibition represses GFP expression [21, 24] confirmed the reduced sensitivity of PDE4B2 T407A to BC54 and rolipram (Fig. 5 B ), although PDE4B T407A appears to be inhibited by high levels of both compounds.…”
Section: Resultsmentioning
confidence: 82%
“…Following the expression of the luciferase reporter into the vector and making the comparison with other promoters such as Pnmt1, Padh1, and AOX1, it was found that lsd90 promoter promotes a constitutive expression of luciferase, at a level of 19-, 39-, and 10-fold higher than the promoters above mentioned, respectively [63]. The urg1 gene was identified as a rapidly induced transcript, responding to uracil addition in ~30 min and exhibiting low off-state transcription and high dynamic range [64] Other useful constitutive promoters in the protein expression are tif471 (with moderate force) and lys7 (weak promoter) [27,65].…”
Section: Heterologous Protein Expressionmentioning
confidence: 99%